THE EVOLUTION OF HEROES AS DEFENDERS OF THE MOTHERLAND IN YURI BONDAREV’S «HOT SNOW» AND SHUKHRAT’S «YEARS IN OVERCOATS» (Proceedings of International Educators Conference, 2024)
This article explores the transformative journeys of protagonists in Yuri Bondarev’s «Hot snow» and Shukhrat’s «Years in overcoats» as they evolve into defenders of their homeland during the Great Patriotic War. Through a detailed comparative analysis, we examine the profound psychological and emotional development of the characters Elmurad and Kuznetsov, highlighting their transitions from youthful idealism to seasoned valor. The narratives, grounded in authentic wartime experiences, illustrate the protagonists’ internal and external struggles, portraying their steadfast courage and patriotism. Additionally, this study delves into the intricate dynamics of comradeship, the influence of personal losses, and the overarching theme of love amidst the chaos of war. The dualities in the characters’ portrayals underscore the complex interplay between individual heroism and collective duty, offering a nuanced understanding of wartime literature’s contribution to the cultural memory of World War II.